2+8x=4(2x+2)-6

Simple and best practice solution for 2+8x=4(2x+2)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2+8x=4(2x+2)-6 equation:


Simplifying
2 + 8x = 4(2x + 2) + -6

Reorder the terms:
2 + 8x = 4(2 + 2x) + -6
2 + 8x = (2 * 4 + 2x * 4) + -6
2 + 8x = (8 + 8x) + -6

Reorder the terms:
2 + 8x = 8 + -6 + 8x

Combine like terms: 8 + -6 = 2
2 + 8x = 2 + 8x

Add '-2' to each side of the equation.
2 + -2 + 8x = 2 + -2 + 8x

Combine like terms: 2 + -2 = 0
0 + 8x = 2 + -2 + 8x
8x = 2 + -2 + 8x

Combine like terms: 2 + -2 = 0
8x = 0 + 8x
8x = 8x

Add '-8x' to each side of the equation.
8x + -8x = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 8x + -8x

Combine like terms: 8x + -8x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -4k=9k | | -5h=-32/3 | | 16x^2-88x+121=0 | | -1x+4=7x-3 | | 8x-73=4x-9 | | 6a-5(8-3a)= | | 4k-8k=-6 | | 38-n=4.7 | | 60=-5r | | 2+4n+7=21 | | 6-8x=98-36x | | 15x=-240 | | 0.12x-0.65=1.28 | | .13-.01(x+1)=-.03(4-x) | | 12(3x+5)-6(2x-2)=4x-68 | | 2x+7=17-10x | | 16-8t=5-9t | | 0.75x+3.22=6.97 | | 1x+4=7x-3 | | 2(x+4)-3=4x-2(-5+x) | | 112-4x=4x-24 | | y+5(y-1)=7 | | (5x-2)(2x)=115 | | -43-2x=17-8x | | 7p+1=5p+25 | | 10=5+2x | | 24x^2+36=4x*h | | 2(c-1)=4(3-c) | | 4x^2+36x=4x*h | | 6x+29x-7=7(5x+4) | | 3y+9=2y-6 | | 6x^2-7x+3=0 |

Equations solver categories